Linking biological and cultural diversity : a novel approach for urban greenspaces planning and management - Gonçalves, Paula Isabel (2022)
Planning and managing ecologically sound and inclusive Urban Green Spaces (UGS) providing meaningful experiences that contribute for visitors well-being is of paramount relevance and requires a deep integration of natural and social sciences knowledge. Drawing on the Biocultural Diversity (BCD) concept, that addresses the close interlinkage between biological and cultural diversity, we developed a conceptual framework adapted to the urban setting, highlighting the three dimensions where these interactions manifest: Lived BCD, Materialized BCD and Stewardship of BCD. These three dimensions were the foundation to develop and operationalize an indicator-based decision tool, which was tested in Lisbon’s twelve parks. Besides proven feasible and useful, the tool allowed to unearth self-exclusion processes. Motivations to visit UGS, and their enjoyed and disliked features, were analysed in 33 parks of four European cities, and related with their structural diversity. Motivations for visit were highly variable and though mostly based on social interactions or physical activities, the most appreciated features were related with the park itself and nature, a result consistent across cities. Parks with lower structural diversity, serving neighbourhoods of lower socioeconomic condition displayed less motivations and enjoyments. One of the benefits of visiting greenspaces is psychological restoration and the study of Lisbon parks showed that this was mainly driven by user’s perceptions, rather than by biodiversity itself, but mediation analysis showed that the effect of proportion of broadleaf species in biodiversity perception was completely mediated by the perception of trees diversity. Overall, this thesis contributed to highlight the usefulness of the BCD concept in urban settings, by developing a conceptual framework and a decision support tool, that revealed environmental justice issues that otherwise would have remained hidden, and by making a major contribution to clarify the mechanisms underlying the influence of urban biodiversity in mental well-being and to contribute to policy at the planning level.